Demonstration of new subtypes of adenovirus 7 in South Africa, and probing oesophageal carcinoma cell lines for evidence of adenovirus or of other oncogenic viruses - Brooks, Louise Alexandra (Department of Medicine, 2017)
This study was carried out in 2 parts: 1. Genome analysis of human adenovirus species 7; 2. Search for a possible viral aetiology in oesophageal carcinoma. Sixteen laboratory isolates of adenovirus species 7, isolated in South Africa between 1975 and 1986, were characterized by restriction endonuclease analysis of their DNA genomes. Virus was propagated in human embryo fibroblast cells; genomic DNA, extracted and purified from cellular DNA extracts, was analyzed using 9 different restriction enzymes. Results of this study have demonstrated 2 new genome types of adenovirus 7c which have not previously been identified. The 2 novel strains, designated as genome types Ad7c1 and Ad7c2, were shown to differ from prototype Ad7 c according to restriction profiles with EcoRI; 2 new EcoRI sites were demonstrated in Ad7c1 and 1 in Ad7c2. The restriction sites were mapped on the viral genomes (at 3.68kb and 5.32kb from the left terminus) by double enzyme digestions, cloning of viral DNA, and nucleic acid hybridization using a cloned Ad7 probe. Strains resembling the prototype Ad7c and Ad7p (Gomen) genome types were also identified in the 1985 and 1986 Ad7 isolates. In order to investigate the possible role of a viral co-factor in the aetiology of oesophageal carcinoma, 18 probes, derived from potentially oncogenic viruses, were used to screen 3 human oesophageal carcinoma cell lines for the possible presence of integrated viral DNA. One of these, an Ad7 recombinant plasmid probe, was developed by cloning DNA from the transforming region of the Ad7cl strain into the plasmid vector pUC19. Cellular DNA, extracted from the 3 tumor lines HCU18, HCU33 and HCU39, was tested by means of both DNA dot hybridization and Southern blot hybridization for the presence of Epstein-Barr virus, human papillomavirus (types 1, 5, 6, 8, 11, 16, 18), human adenovirus (strains 5, 7, 12, 31) and human T-lymphotropic virus type I DNA. Both assays were demonstrated to be sensitive enough to detect 1 copy of viral DNA per cell. No hybridization between HPV, EBV, HTLV-I or adenovirus DNA probes, and the cellular DNA was detected. These findings indicate that the stable integration of these tumor viruses in host chromosomes did not play a role in the maintenance of the malignant phenotype of the 3 extensively passaged cell lines. Cells of the 3 oesophageal tumor lines were further examined by transmission electron microscopy, but the presence of virus particles in these cells was not observed.